A Case of LGI1 Encephalitis Presenting with NORSE - Gökberk Metin; Özden Kamışlı (Archives of Epilepsy, 2024)

(untitled)
New-onset refractory status epilepticus (NORSE) is a rare, life-threatening clinical presentation in patients without a known history of epileptic seizures. Autoimmune encephalitis is the most common cause identified in adults; however, in up to 50% of cases, no cause can be found. We present a case of a previously healthy 26-year-old male admitted to the intensive care medicine with NORSE, whose condition improved with the initiation of immunotherapy. Later, he was diagnosed with anti-leucine-rich glioma-inactivated 1 (anti-LGI1) antibody encephalitis. Despite prompt initiation of immunotherapy, cognitive function deterioration and resistant seizures persisted. NORSE is a critical condition that requires urgent treatment. In patients with a negative initial work-up, a preliminary diagnosis of autoimmune encephalitis should be considered. It is critical to begin immunotherapy before the autoimmune encephalitis panel results, as early treatment improves outcomes and long-term prognosis.